2010
DOI: 10.1111/j.1463-1318.2010.02269.x
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery is superior to transanal excision of rectal adenomas

Abstract: Transanal endoscopic microsurgery is superior to transanal excision of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(67 citation statements)
references
References 23 publications
2
58
0
5
Order By: Relevance
“…We were unable to clarify these doubts because we received no reply to our request from the respective study authors. In all, 21 studies met the inclusion criteria for a total of 2,077 patients: 11 ESD series [11][12][13][14][15][16][17][18][19][20][21] totaling 536 patients, and 10 TEM series [2,[22][23][24][25][26][27][28][29][30], totaling 1,541 patients. …”
Section: Resultsmentioning
confidence: 99%
“…We were unable to clarify these doubts because we received no reply to our request from the respective study authors. In all, 21 studies met the inclusion criteria for a total of 2,077 patients: 11 ESD series [11][12][13][14][15][16][17][18][19][20][21] totaling 536 patients, and 10 TEM series [2,[22][23][24][25][26][27][28][29][30], totaling 1,541 patients. …”
Section: Resultsmentioning
confidence: 99%
“…21 These findings were reproduced in other studies. De Graaf et al 22 compared TAE to TEM for adenomas and had similar findings with regard to fragmentation and resection margins. Interestingly, patients with positive margins in the TEM group had lower recurrence rates than did patients with positive margins in the TAE group (7% vs 59.6%, respectively), concluding that TEM is superior to TAE for rectal adenomas.…”
mentioning
confidence: 61%
“…Interestingly, patients with positive margins in the TEM group had lower recurrence rates than did patients with positive margins in the TAE group (7% vs 59.6%, respectively), concluding that TEM is superior to TAE for rectal adenomas. 22 A recently published systematic review and meta-analysis by Clancy et al 23 compared recurrence rates and pathologic outcomes between TEM and TAE. The authors demonstrated that patients undergoing TEM had a higher rate of negative margins, less specimen fragmentation, and lower lesion recurrence rates with similar complication profiles for both the procedures, but without any significant differences between the groups.…”
mentioning
confidence: 99%
“…All patients after TEM are in a postoperative surveillance protocol which includes rigid proctoscopy (plus endorectal ultrasound in a group with invasive cancer) every 3 months during first two years. So far, no recurrent or progressing disease has been found TEM seems to be a satisfactory alternative to trans-anal excision or major abdominal resection for removal of benign rectal lesions However, regardless of a number of articles in the current literature, the superiority of TEM compared to transanal excision was not demonstrated until recently, when de Grafet al [6] demonstrated a statistically significant difference comparing postoperative morbidity between the two procedures (5 3% and 10% respectively). The superiority of either trans anal excision or TEM compared to abdominal resection has been recorded by many authors including Langer et al [7], who however did not show a statistically significant difference in this respect between the two options of trans anal approach.…”
Section: Resultsmentioning
confidence: 97%